Development and Performance Evaluation of Silicone-Based Hydrophobic Coatings for Anti-Soiling Applications on Solar PV Glass - Ahmad A. Thaiubudeen; Shaharin A. Sulaiman; Syed Awais Ali Awais (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Soiling is a major cause of performance degradation in solar photovoltaic (PV) systems, particularly in tropical environments characterized by high humidity and persistent dust accumulation. This study presents the development and experimental evaluation of silicone-based hydrophobic coatings designed to enhance the anti-soiling and water-repellent properties of PV glass substrates. Three coating formulations with varying silicon dioxide (SiO2) nanoparticle contents, 2.03 wt% (HC1), 3.34 wt% (HC2), and 0 wt% (HC3), were prepared and systematically characterized. Coating performance was assessed using water droplet mobility tests, static water contact angle (WCA) measurements, and controlled dust-accumulation experiments. Among the formulations, HC2 exhibited the best overall performance, achieving the highest average WCA (94.3°), fastest droplet runoff time (0.8 s), and lowest dust accumulation (4.4 mg). The results confirm that increasing SiO2 nanoparticle concentration enhances surface hydrophobicity and reduces dust adhesion by modifying surface roughness. These findings highlight the potential of optimized silicone-SiO2 coatings as a cost-effective, passive anti-soiling solution for improving the operational efficiency of solar PV systems, particularly in dust-prone environments.